EFEKTIVITAS CITY BRANDING “NEGERI INDAH KEPINGAN SURGA” TERHADAP KUNJUNGAN WISATAWAN KE KABUPATEN SAMOSIR - Nasution, Ridwan; Parhusip, Lasdame (Ilmu Komunikasi, FISIP Universitas Pasundan, 2024)
ABSTRACT The concept of city branding is a strategy studied to introduce a region to the public. The important thing in this branding is to change the mindset and view of a city. The Regional Government of Samosir Regency established a branding that is considered capable of introducing the potential of the region with the tagline